Anal Cancer Prevention in a High-risk Population - Pack, Aaron E.; Voskuhl, Gene W. (Journal for nurse practitioners, 2015)
Anal cancer is an uncommon disease that is occurring more frequently each year in the United States, disproportionately affecting patients with human immunodeficiency virus and men who have sex with men. The natural history of anal cancer is thought to mimic that of cervical cancer, with human papillomavirus infection progressing to anal dysplasia and invasion of cancer in susceptible individuals. Screening for anal cancer is an easy, cost-effective intervention in high-risk individuals, but, with few clinicians specializing in the diagnosis and treatment of anal dysplasia, some planning is necessary. Patients with abnormal cytology or physical examination should be referred for specialist care. •Anal cancer is uncommon, but has an up to ninefold risk in some populations.•Annual anal Pap smear testing is easy and cost-effective.•Abnormal cytology or physical exam findings require HRA referral.•HPV vaccination is woefully underused in young men with only 14% fully covered.•NPs can treat anogential warts in the office, but need a low threshold for referral.